Pressure dependence of the emission in CaF2 : Yb2+. (14th July 2015) - Mahlik, S; Lazarowska, A; Grinberg, M; Wells, J-P R; Reid, M F
Abstract: We present a detailed spectroscopic investigation of CaF2 doped with Yb 2+ performed at high hydrostatic pressure which is applied in a diamond anvil cell. At ambient pressure and at temperatures lower than 175 K, the luminescence consists of a single broad band peaked at 18 500 cm −1, attributed to the recombination of impurity-trapped excitons. Increasing pressure causes the luminescence to be observable at higher temperature. At a pressure of 72 kbar luminescence can be observed up to 275 K. The emission lineshape does not strongly depend on pressure below 85 kbar. However, at 85 kbar it is blue shifted to 21 630 cm −1 . This is attributed to the known phase transition of the CaF2 crystal from cubic to the orthorhombic phase. The absolute energy of the ground and 4f 13 5d states of Yb 2+ as well as the energy of the impurity-trapped exciton with respect to valence and conduction bands have been estimated. The results, are discussed in comparison with the pressure dependences observed for the luminescence of BaF2 : Eu 2+ and CaF2 : Eu 2+ . The difference between the spectral properties of Eu 2+ and Yb 2+ is attributable to the fact that the ground and 4f 6 5d states of Eu 2+ are placed deeper in the CaF2 bandgap than the ground and excited 4f 13 5d states of Yb 2+, whereas the energies of the impurity-trapped exciton states for Yb 2+ and Eu 2+ with respect to the conduction band are approximately the same.